Characterization of a P-Rex1 gene signature in breast cancer cells - Barrio Real, Laura (2016)
The Rac nucleotide Exchange Factor (Rac-GEF) P-Rex1 is highly expressed in breast cancer, specifically in the luminal subtype, and is an essential mediator of actin cytoskeleton reorganization and cell migratory responses induced by stimulation of ErbB and other tyrosine-kinase receptors. Heregulin (HRG), a growth factor highly expressed in mammary tumors, causes the activation of P-Rex1 and Rac1 in breast cancer cells via ErbB3, leading to a motile response. Since there is limited information about P-Rex1 downstream effectors, we carried out a microarray analysis to identify genes regulated by this Rac-GEF after stimulation of ErbB3 with HRG. In T-47D breast cancer cells, HRG treatment caused major changes in gene expression, including genes associated with motility, adhesion, invasiveness and metastasis. Silencing P-Rex1 expression from T-47D cells using RNAi altered the induction and repression of a subset of HRG-regulated genes, among them genes associated with extracellular matrix organization, migration, and chemotaxis. HRG induction of MMP10 (matrix metalloproteinase 10) was found to be highly sensitive both to P-Rex1 depletion and inhibition of Rac1 function by the GTPase Activating Protein (GAP) β2-chimaerin, suggesting the dependence of the P-Rex1/Rac1 pathway for the induction of genes critical for breast cancer invasiveness. Notably, there is a significant association in the expression of P-Rex1 and MMP10 in human luminal breast cancer, and their coexpression is indicative of poor prognosis. Brecha entre expectativas y percepciones de los empleadores: Un aspecto importante a tener en cuenta al analizar la brecha fue considerar no sólo la evaluación actual sino también la expectativa sobre el atributo bajo análisis. En tal sentido, una brecha amplía podría deberse tanto a una buena evaluación como a una baja expectativa. Los resultados expuestos revelaron, en concordancia con el análisis respecto de la satisfacción general de los empleadores con los graduados de la Licenciatura en Economía, que la totalidad de las brechas analizadas están dentro de la zona de satisfacción. Las brechas de las variables con mayor expectativa sobre las competencias de los graduados referidas a cada uno de los grupos definidos, es decir, la capacidad para la identificación de problemas y encontrar la solución, la capacidad para acceder, evaluar y sintetizar información y la capacidad para pensar crítica, creativa y reflexivamente si bien no alcanzan el nivel de satisfacción total, cumplen con las expectativas de los empleadores. Adicionalmente, las brechas de las variables en las cuales los empleadores se han mostrado algo más que satisfechos fueron aquellas en las que las expectativas no eran demasiado altas al momento de realizar la encuesta.